E-Government Solutions in Poland: The State of E-Services Provided by a Selected Local Government Unit - Kołodziej, Dominika (Journal of Public Governance, 2023)
Objective: The subject of the article is an attempt to determine the state of e-government development in local government units in Poland based on the example of the selected Piekary Śląskie City Hall, operating in the Śląskie voivodeship. The aim of the paper is to explain the state of e-government, then to present the applied IT tools and solutions in local government units in Poland, and make an attempt to assess the state of application of e-government solutions at the local level in a selected local government unit through the perspective of e-service provision according to the maturity model. Research Design & Methods: In this study, the method of deduction was used as well as auxiliary methods and techniques such as logical analysis, analysis and study of literature, and classification and scientific description. In order to perform the research task, the applied empirical procedure was supported by a critical review of the literature on the subject in Polish and English, and practical cooperation with a selected local government unit. The research part of the study used non-participant observation, a case study and a face-to-face interview. In order to obtain information, the Polish electronic platform for public administration services (ePUAP) of the Piekary Śląskie City Hall was analysed and an interview with an employee of this unit was conducted in July 2023. Findings: The results of the conducted scientific analysis show that IT and technological solutions and tools have a significant impact on the effective e-government functioning. In addition, these factors reflect access to e-services provided by public administration, as well as employee and customer competence with regard to e-government. Implications/Recommendations: The results of the scientific analysis and its findings contribute to existing research by providing knowledge on the state, progress, and development of e-government through the provision of e-services provided by public administration in a selected local government unit in the Śląskie voivodeship. Contribution/Value Added: The research shows that the interest in the development of e-government among researchers is great, because the topic is still up-to-date and has utilitarian values. The assessment of public e-services in a selected local government unit (i.e. the Piekary Śląskie City Hall) makes it possible to determine the level of the maturity at which the examined unit is located. The study may also serve as a introduction to and a basis for a comprehensive diagnosis of the state of application of IT and technological tools and e-government development in all local government units in Poland.